The study protocol for a multicenter observational headache registry: Brazilian Headache Registry - REBRACEF II: Registro Brasileiro de Cefaleia - REBRACEF II - Souza, Jesuély Spieckert de; Antunes, Marcos Otávio Brum; Oliveira, Vinícius da Silva Lessa de; Hammes, Jordana Henz; Barros, Lígia; Vieira, Rebeca Veras de Andrade; Jurno, Mauro Eduardo; Friedrich, Frederico; Grassi, Vanise (Headache Medicine, 2024)
ObjectiveThis article presents the protocol for the Brazilian Headache Registry (REBRACEF), the first national registry designed to systematically collect real-world data on patients with primary and secondary headaches at specialized centers in Brazil. The main objective is to describe the methods for patient selection, the registry infrastructure, data collection, and the standardized instruments used.MethodologyREBRACEF is a prospective, observational, multicenter cohort study conducted in real-world settings.Expected resultsThis protocol aims to standardize and enable the structuring of the registry, allowing its implementation in other centers across Brazil. It also ensures external feasibility by establishing a robust framework that can be replicated in other national and international healthcare institutions.ConclusionThe registry protocol provides a standardized framework for the collection of real-world data on patients with primary and secondary headaches, facilitating the improvement of headache management and research in Brazil.